Seismic Stratigraphy Of The Makassar Basin - Dr. B Situmorang (Testing Center for Oil and Gas LEMIGAS, 1987)
Seismic reflection profiles from the Makassar basin have been analysed in terms of seismic stratigraphy. Systematic patterns of reflection terminations indicate the existence of at least three surfaces of discontinuity across the profiles-designated in order of superposition as C1, C2 and C3 - which define the boundaries of four seismic sequences, ie. :- seismic sequence I : topped by C1- seismic sequence II : the interval between C1 and C2- seismic sequence III : the interval between C2 and C3- seismic sequence IV : the interval between Cz and the sea floor Seismic sequence II is dominated by basin slope and basin floor seismic facies whereas seismic sequences II and IV consist of mainly shelf and shelf margin seismic facies. Correlation of seismic sequences with well data facilitates the exposition of basin development, The Late Cretaceous-early Tertiary regional uplift and erosion produced a major unconformity C1, upon which the transgressive facies of seismic sequence II was deposited. A lowstand of sea level due to the so-called intra-Mio- cene orogeny occurred in the upper Early Miocene and produced the C2. Deposition of seismic sequence III is marked by a relative rise of sea level, probably followed by another lowstand of sea level during Mio-Pliocene which formed the C3. The final event is an overall transgression and deposition of seismic sequence IV, with a possible minor lowstand of sea level in Pliocene-Recent, The occurrence of basin slope and basin floor seismic facies within seismic sequence II suggests that in the pre-Lower Miocene, basin subsidence was slightly greater than the rate of depositions. Since Lower Miocene both subsidence and sedimentation rates were equal and the deposition of shelf and shelf margin seismic facies of seismic sequences III and IV was prevailed in the basin.